NEW DIMENSIONS OF THE CHILD-CURRICULUM RELATIONSHIP IN THE CONCEPTION OF THE AUTHOR JOHN DEWEY - Marius Costel ESI (International Journal of Social and Educational Innovation, 2022)
The education is the result of the experience of culture which the child can amass and assimilate under certain conditions. Thus, the curriculum should guide the child's experience taking into account the shortest paths. However, the reference to the past should only be considered as a form of departure in what will later be the child's true experience. The experience is the result of all that humanity has accumulated over time forming ongoing experiences through a permanent process of cultural reconstruction. In other words, education is the very reconstruction of experience in relation to the previous experience.